Learning Communities AD Hoc Task Force Final Report - Geoffrey Buhl::::::; Dennis Downey::::::; Tiffany Elliott::::::; Gary Gordon::::::; Venessa Griffith::::::; Veronica Guerrero:::Chair:::; HyeSun Lee::::::; Susan Lefevre:::::: (2022)
This report is the culmination of work completed by the ad hoc task force for the charge of Scaling Learning Communities at CSUCI for the AY2023/34. The report provides an overview of the process for this work and the final recommendations for consideration in scaling of the learning communities to reach the target of 70% enrollment of first-time, full-time students (FTFT) in Fall 2023. The charge for this call can be found in Appendix A.To provide context to this work, the Learning Communities for the AY22/23 includes 311 enrolled students at the beginning of the Fall 2022 semester. This includes 12 learning/living communities for a total of 19 cohorts (some cohorts have multiple sections), and there are 12 to 20 students enrolled in each cohort. This is an increase of 45% from Fall 2021, when there were 9 learning/living communities for a total of 12 cohorts, total of 140 students. If the Fall 2023 incoming first time freshman class is 600 students, the goal is to enroll 420 of these students into a learning community. This would increase participation by about 35% or 109 students over the current year. In the current year, the Learning Communities team recruited and trained 19 embedded peer mentors (EPM). The goal was to hire 25 EPMs (anticipating 350400 students in LCs), but they were not able to fill all open positions. The EPM team is central to the Learning Community programming. You will find this highlighted in the recommendations in this report.